GABA-Aα5 Might Be Involved in Learning-Memory Dysfunction in the Offsprings of Chronic Ethanol-Treated Rats via GABA-Aα5 Histone H3K9 Acetylation - Zeng, Kuan; Xie, Aimin; Dong, Xiaojie; Jiang, Jia; Hao, Wei; Jiang, Min; Liu, Xuebing (Frontiers in Neuroscience, 2019)
Recent studies has been focused on the relationship between GABA-Aα5 and alcohol induced spatial learning and memory deficits. In this study, we demontrated that the chronic ethanol treatment increased the expression of GABA-Aα5 by its histone H3K9 acetylation in gene. Furthermore, this epigenetic modification can be inherited by the next generations and led to GABA-Aα5 expression upregulation, which eventually exhibit similar spatial learning and memory deficits in the offspings. Our results shed light on the possible mechanisms to alcohol addiction and its inheritation pathway. Hopefully in the near future, GABA-Aα5 inhibitors would be a new way to treat alcohol induced conginition impairment.